“In Search of Spirituality: A Deliberative Approach.” (Theological Kronos, 2020)
Western spirituality has suffered the onslaught of criticism and has been reduced to mere reason or feeling. The icons that were of absolute value and underpinned spirituality, these icons have been knocked down. However, the mere reason has been found insufficient and limited when satisfying the search for “meaning” of the human beings. The following article tries to contribute my reflections on the matter and evoke a proposal in favor of the inwardness from criticism.
Keywords: Criticism; inwardness; deliberation; quest; meaning